Moisture as a key factor alleviating low-temperature stress: Effects of hydrothermal conditions on maize emergence - Yang HuiYing; Gao Pan; Xu YingYing; Zhang GongLiang; Zheng Xu; Jiang Yu; M.I. Gang; Wang YuXian (PLoS ONE, 2026)
Early spring sowing of maize in semi-arid, wind-eroded regions is increasingly threatened by cold snaps due to climate change.These events, often coupled with uneven soil moisture distribution,compromise seedling emergence and early development. Identifying critical temperature and moisture thresholds is essential to ensure successful germination in these vulnerable environments.A factorial experiment was conducted in a controlled environment using maize seeds (Zea mays L.) exposed to diurnal temperature cycles.Treatments included five minimum temperatures (0,2,4,6,8°C), three chilling durations (2,4,6 hours),and four soil moisture levels (60,70,80,90% field capacity). Key germination metrics,including final germination rate, weighted germination time,synchrony,delay days,and seedling dry matter at day 30,were measured and analyzed using three-way ANOVA and Pearson correlations. Temperatures below 6°C significantly delayed germination and reduced final germination rates,particularly under low moisture conditions.Moisture levels ≥80% effectively mitigated chilling effects at moderate temperatures(4 ~ 6°C).Extended chilling durations further suppressed germination.The strongest interaction was observed between minimum temperature and soil moisture.Seedling dry matter accumulation was also significantly affected by all three factors and their interactions.Soil moisture serves as a critical buffer against chilling stress during maize germination. This study provides quantitative benchmarks for temperature and moisture combinations that optimize early maize emergence under extreme spring weather, offering practical insights for precision moisture management in semi-arid agriculture.